Off-Label Use of Ataluren in Four Non-ambulatory Patients With Duchenne Muscular Dystrophy: Effects on Cardiac and Pulmonary Function and Muscle Strength - Ebrahimi-Fakhari, Daniel; Dillmann, Ulrich; Flotats-Bastardas, Marina; Poryo, Martin; Abdul-Khaliq, Hashim; Shamdeen, Mohammed Ghiath; Mischo, Bernhard; Zemlin, Michael; Meyer, Sascha (Frontiers in Pediatrics, 2018)
About 15% of Duchenne muscular dystrophy (DMD) cases are caused by point mutations leading to premature stop codons and disrupted synthesis of the dystrophin protein. Stop codon read-through therapy is available with the drug Ataluren (Translarna® by PTC Therapeutics). Following positive results in ambulatory nmDMD (non-sense mutation Duchenne muscular dystrophy) patients, Ataluren received conditional approval in ambulant nmDMD patients by the EMA in 2014. However, there are limited data on non-ambulatory nmDMD patients treated with Ataluren. Here, we report our experience in four non-ambulatory DMD patients. Routine investigations included cardiac function, pulmonary function tests and muscle strength. We compared changes in left ventricular fractional shorting, forced volume vital capacity and BMI from two defined time periods (18–26-month period prior to and after Ataluren start). Mean age at loss of ambulation was 10.1 ± 0.5 years, mean age when initiating Ataluren treatment 14.1 ± 1.4 years. Serial echocardiography, pulmonary lung function tests, and assessment of muscle strength indicated mild attenuation of disease progression after initiation of Ataluren treatment. A possible side effect of Ataluren was a reduction in BMI. There were no adverse clinical effects or relevant abnormalities in routine laboratory values. We conclude that Ataluren appears to mildly ameliorate the clinical course in our patients with a good safety profile. However, larger clinical trials are required to assess the role of Ataluren and its long-term impact on disease progression in non-ambulant nmDMD patients.